Microplastic contamination in different tissues of commercial fish in estuary area - N.D. Takarina; O.M. Chuan; A. Adiwibowo; F.N.A. Jeffery; N.Z.A.B.N.M. Zamri; M.A. Adidharma (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The coasts around West Java, Indonesia are prospective fishing grounds due to their commercial fish diversity. The presence of neighboring settlements discharging waste, including microplastics, poses a threat to the estuarine ecosystem. This study aimed to quantify and classify microplastics in the tissues of Mugil cephalus, Eleutheronema tetradactylum, and Scatophagus argus.METHODS: This study takes place in the estuary of the Blanakan River, Subang Regency, an area renowned for its wide variety of commercially valuable fish. Four fish sampling sites were identified according to the predominant land use, with settlements in the upper reaches, ponds in the central area, and mangrove forests in the lower reaches. Fish samples were taken the gastrointestinal tract, gills and muscle to calculated the microplastic content and identify its shape and size. Raman spectroscopy was applied to verify the polymer of microplastic. Statistical analysis was conducted to evaluate variations in microplastic levels at the individual level across these  fish species.FINDINGS: The findings indicated the presence of microplastics in the muscle, gastrointestinal tract, and gills of three commercially caught fish from Blanakan, with the muscle being identified as the edible part and the gastrointestinal tract and gills as the non-edible parts. The microplastics were classified according to shape and size and were found in the following order of abundance: Mugil cephalus, Scatophagus argus, Eleutheronema tetradactylum. Mugil cephalus contained the most microplastics (210.8 particles per individual), with the lowest amount recorded in Eleutheronema tetradactylum (41.9 particles per individual). The tissues of Eleutheronema tetradactylum exhibited varying levels of microplastic contamination, with the highest concentration found in the gastrointestinal tract, followed by the gills and muscles. In contrast, in the tissues of Mugil cephalus and Scatophagus argus, microplastics were found in the following order of abundance from high to low: muscle, gastrointestinal tract, gill. The muscle of Mugil cephalus contained the highest microplastic concentration (28.71 particles per gram wet weight), while the lowest was recorded in the muscle of Eleutheronema tetradactylum (3.42 particles per gram wet weight). Microplastics ranging from 300 to 1000 micrometers in size, in the form of fibers and fragments, were commonly found in fish tissues.CONCLUSION: Microplastic content is found most abundantly in the gastrointestinal tract and muscle. This indicates that feeding and ingestion play a role in the entry of microplastics into the fish's body. Given that the fish falls under the category of commercial and consumption fish, there is a significant concern regarding environmental pollution caused by microplastics and the potential health hazards linked to its consumption.